Potential for the application of dynamic skin thermography after local hypothermia - I. A. Novikov; S. Yu. Petrov; E. S. Rein; Т. Е. Borisenko; S. V. Sdobnikova; E. E. Lucevitch; S. E. Avetisov (Biomedical Photonics, 2019)
Infrared thermography is one of the widely used non-invasive diagnostic methods. While the procedure is mainly used for early malignant tumor diagnostics, a potential application for thermography was proposed in cardiovascular, skin, autoimmune diseases, arthritis, Reynaud’s syndrome, burns, surgery and therapeutic treatment monitoring. The method of thermographic evaluation has not changed significantly since the end of 20th century. In this study we attempted to characterize the influence of skin capillary blood flow on surface temperature recuperation following local hypothermia. To improve sensitivity and standardize the procedure we developed a study protocol that involves minimizing or excluding the influence of external factors on study results. An original applicator was used to apply dosed hypothermia. Massive porcine tissue block was chosen as a passive model without active heat and mass transfer but with heat capacity, structure and heat dissipation characteristics similar to human tissues. 51 healthy volunteers were assigned to control group, while 16 patients with diabetes mellitus constituted the main study group. Cumulative temperature difference was calculated in all cases. It was 121,8 ± 70,8 °С×s in the control group, 95,6 ± 54,4 °С×s in the main study group and 307,2 ± 43,4 °С×s in the passive model. Based on the study results, we made the following conclusions: absence of heat and mass transfer in the passive model complicates heat balance recuperation due to layered structure of the skin; heat balance recuperation curve is an individual parameter and is not influenced by age or gender.